Ami??lcar Cabral and the PAIGC's Binational Struggle for the Independence of Guinea-Bissau and Cabo Verde - Barros, Vi??ctor, author. Link
1 online resource
Keywords: The struggle for independence of Guinea-Bissau and Cabo Verde was shaped by a multiplicity of interactions and connections. Because of the intimate association between the African Party for the Independence of Guinea and Cabo Verde (PAIGC - Partido Africano da Independ????ncia da Guin????? e Cabo Verde) and Am????lcar Cabral's leadership, the existing scholarship has been discussing the fight led by the liberation movement and its Secretary-General's role within a single analytical framework.While much has been written, most studies fail to break the many historiographical silences still existing around the subject. Am????lcar Cabral and the PAIGC's Binational Struggle for the Independence of Guinea-Bissau and Cabo Verde intends to evince a multiplicity of analytical itineraries through which Cabral's figure can contribute to understand the rise to statehood of both territories and the construction of memory of the anti-colonial struggle.